2022
DOI: 10.1186/s40001-022-00861-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of sputum cells reveals two distinct molecular phenotypes of “asthma and chronic obstructive pulmonary disease overlap” in the elderly

Abstract: Background Little is known about the pathogenesis of asthma and chronic obstructive pulmonary disease (COPD) overlap (ACO). This study examined the molecular phenotypes of ACO in the elderly. Methods A genome-wide investigation of gene expression in sputum cells from the elderly with asthma, ACO, or COPD was performed using gene set variation analysis (GSVA) with predefined asthma- or COPD-specific gene signatures. We then performed a subsequent cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…55 A recent transcriptomic study of asthma-COPD overlap (ACO) has reported a cluster of ACO that had features of mitochondria and peroxisome dysfunction. 56 Certainly, the relationship between mitochondrial function, peroxisomes, oxidative stress and inflammation in COPD warrants further investigation in its role in lung function decline.…”
mentioning
confidence: 99%
“…55 A recent transcriptomic study of asthma-COPD overlap (ACO) has reported a cluster of ACO that had features of mitochondria and peroxisome dysfunction. 56 Certainly, the relationship between mitochondrial function, peroxisomes, oxidative stress and inflammation in COPD warrants further investigation in its role in lung function decline.…”
mentioning
confidence: 99%